FIELD IMPLANTATION OF INTRAPERITONEAL RADIOTRANSMITTERS IN EASTERN WOLF (CANIS LYCAON) PUPS USING INHALATION ANESTHESIA WITH SEVOFLURANE - Crawshaw, Graham J.; Mills, Kenneth J.; Mosley, Craig; Patterson, Brent R. (Journal of wildlife diseases, 2007)
In a study of wolf pup survival, intraperitoneal radio transmitters were surgically implanted in 53 (27 male and 26 female) 3.5- to 8-wk-old Eastern wolf (Canis lycaon) pups at den sites in Algonquin Provincial Park, Ontario, Canada, over two whelping seasons (2004 and 2005). Pups were manually removed from dens and initially injected with butorphanol at a dosage of 0.1 mg/kg for sedation and intra-operative analgesia. Anesthesia was induced and maintained with 3% sevoflurane in oxygen via a face mask. Meloxicam (0.3 mg/kg intramuscularly) was given to provide additional analgesia. All surgeries were completed without complications, and pups were readily accepted back into the packs. No postoperative complications were identified, but two pups from a single litter drowned as a result of being moved by the pack to a flooded den following the surgery. In five pups necropsied following natural deaths, transmitters were found lying free within the peritoneal cavity, and there was no evidence of infection at the surgical site or peritonitis. Inhalation anesthesia provided extremely rapid induction (1 min) and recovery (<3 min) and was completely controllable with no residual anesthetic effects. The equipment for inhalation anesthesia was readily portable in field packs, and it has considerable advantages over injectable drugs for small and very young animals such as wolf pups. The utility of the procedure is demonstrated by the minimal effect it had on subsequent pup survival, the rapid recovery of pups following surgery, and the lack of long-term complications as determined by necropsies of pups following natural deaths.